Congestion Management: From Physics to Regulatory Instruments - Lion Hirth; Samuel Glismann (ZBW – Leibniz Information Centre for Economics, 2018)
In recent years, power flows in many European transmission and distribution networks have increased, making the management of network congestion a much-debated – and increasing politicized – topic. This paper is an introduction to and a review of congestion management in European electricity grids. We review the physical measures available to avoid congestion, using a newly introduced analytical framework. Also, we provide a com-prehensive review of regulatory instruments used and proposed to incentivize those measures. Finally, we provide a description of the implementation of three prominent instruments, including so-called redispatch.
Keywords: 330; Redispatch; Congestion Management